Developing “Makruf (Mahir Makhorijul Huruf)” as Supplementary Learning Media for IX Grade of Junior High Students - Maarif, Iin Baroroh; Rohmah, Hidayatur; Habibi, Abdulloh Husnan (APPLICATION: Applied science in Learning Research, 2023)
This research aims to develop the "MAKRUF" (Mahir Makhorijul Huruf) as learning media for Islamic Education (PAI) subjects with makhorijul huruf material. It also aims to make it easier in understanding makhorijul huruf to support the ability of IX grade students in reading the Holy Qur'an. This research uses the ADDIE (Analyze, Design, Development, Implementation and Evaluation) method. The R&D research method is containng a series of analyzing, designing, developing products, implementing development results and evaluating the results of implementation. This research showed that the media development of "MAKRUF" was declared valid by obtaining a validity percentage of 97% and a very valid category, both from the media validator and material validator perspective. So that the results of developing the "MAKRUF" media are suitable for use as learning media. Keywords: Learning media; Makhorijul Huruf; Junior High; Students